UJI KEOPTIMALAN METODE KSAM UNTUK MENYELESAIKAN SOLUSI AWAL MASALAH TRANSPORTASI - Dhurun Mudhi Zayyan; Rihatul Janah; Aris Alfan (Jurnal Matematika dan Sains (JMS), 2021)
Production activities are closely related to business actors or economic actors who must apply economic principles. It is from this principle that the optimization problem arises. This problem can be solved in various ways, one of which is linear programming. The transportation method is one of linear programming. This method is used to adjust the distribution from sources that provide the same product to the destination optimally. The method of transportation is an important component in its operations because it greatly affects the costs incurred in product distribution. The transportation method has two stages of completion, the first is determining the initial solution and the second is determining the optimal solution. KSAM is a new method formulated to solve transportation problems. The KSAM (Karagul-Sahin Approximation Method) method that was recently introduced is said to provide fairly good performance compared to other methods. From the transportation problem that is addressed in this article by comparing several methods, it is found that the KSAM method provides the best solution with a fairly large solution deviation. then this method can be used as a reference to get the optimal solution.